การพัฒนาความรู้ด้านไวยากรณ์และความสามารถด้านการเขียนภาษาอังกฤษ ของผู้เรียนโดยใช้กระบวนการสอนเขียนตามรูปแบบของ Brookes and Withrow - โชติชัย, บรรจบ; ทาวงศ์ษา, กิตติพัฒน์; อภัยโส, พลภัทร; สาริยา, วันชัย; ศรีโนนยาง, ประดิษฐ์ (วารสารศรีล้านช้างปริทรรศน์, 2018)
งานวิจัยฉบับนี้มีวัตถุประสงค์เพื่อ 1) เพื่อศึกษาระดับความรู้ด้านไวยากรณ์ก่อนและหลังการจัดการเรียนรู้โดยใช้กระบวนการสอนเขียนตามรูปแบบของ Brookes and Withrow 2) เพื่อเปรียบเทียบความสามารถในการเขียนภาษาอังกฤษก่อนและหลังกระบวนการสอนเขียนตามรูปแบบของ Brookes and Withrow  และ 3) เพื่อศึกษาความพึงพอใจต่อการจัดการเรียนรู้โดยใช้กระบวนการสอนเขียนตามรูป แบบของ Brookes and Withrow กลุ่มเป้าหมายเป็นนักศึกษาชั้นศึกษาศาสตรบัณฑิตปีที่ 3 ที่กำลังศึกษารายวิชา ทักษะการเขียนภาษาอังกฤษ (English Writing Skills) รหัสวิชา ED1087 จำนวน 24 คน ในภาคเรียนที่ 2 ปีการศึกษา 2560 เครื่องมือที่ใช้ในการวิจัยเป็น 1) แบบวัดความรู้ด้านไวยากรณ์ จำนวน 80 ข้อ ซึ่งออกแบบมาให้สอดคล้องกับกระบวนการสอนเขียนตามรูปแบบของ Brookes and Withrow 2) แบบวัดความสามารถด้านการเขียนภาษาอังกฤษ ซึ่งเป็นบทความต้นฉบับ จำนวน 20 บทความ จากหนังสือ 10 Steps: Controlled Composition for Beginning and Intermediate Language Development พิมพ์ครั้งที่ 2 (Brookes, G., and Withrow, J. 1996). และ 3) แบบวัดความพึงพอใจ ที่เป็นแบบมาตราส่วนประมาณค่า 5 ระดับของลิเคิร์ท สถิติที่ใช้ในการวิจัยข้อมูลประกอบด้วยค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าทีแบบไม่เป็นอิสระจากกัน         ผลการวิจัยพบว่า         1) ความรู้ด้านไวยากรณ์ของนักศึกษาชั้นศึกษาศาสตรบัณฑิตปีที่ 3 สาขาวิชาการสอนภาษาอังกฤษ หลังการจัดการเรียนการสอนโดยใช้กระบวนการสอนการเขียนภาษาอังกฤษตามรูปแบบของ Brookes and Withrow สูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05         2) ความสามารถด้านการเขียนภาษาอังกฤษของนักศึกษาชั้นศึกษาศาสตรบัณฑิตปีที่ 3 สาขาวิชาการสอนภาษาอังกฤษ หลังการจัดการเรียนการสอนโดยใช้กระบวนการสอนการเขียนภาษาอังกฤษตามรูปแบบของ Brookes and Withrow สูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05         3) ความพึงพอใจต่อการจัดการเรียนการสอนโดยใช้กระบวนการสอนการเขียนภาษาอังกฤษตามรูปแบบของ Brookes and Withrow อยู่ในระดับมาก         The objectives of the research were 1) to study the student’s grammatical knowledge before and after Brookes and Withrow’s approach in English writing teaching, 2) to compare the student’s English writing competence before and after Brookes and Withrow’s approach in English writing teaching, and 3) to study the student’s satisfaction with learning through Brookes and Withrow’s approach in English writing teaching. The target group of the research was a total of 24 third-year students studying the subject – English Writing Skills (ED1087) – in the second semester of the academic year 2017. The instruments of the research were 1) the 40-item pretest and posttest for the student’s grammatical knowledge, designed in accordance with Brookes and Withrow’s model in English writing process 2) the 10-article pretest and posttest for the student’s English writing competence, taken from Brookes and Withrow’s 10 Steps: Controlled Composition for Beginning and Intermediate Language Development, and 3) the student’s satisfaction form, which was Likert’s five-point rating scale questionnaire. The statistics used for data analysis were comprised of mean, standard deviation and the t-test for Dependent Samples.         The research findings were as follows:         1) The grammatical knowledge of the third-year English teaching students after learning through Brookes and Withrow’s model in English writing process wasfound to be higher than before learning at a statistically significant level of .05.         2) English writing competence of the third-year English teaching students after learning through Brookes and Withrow’s model in English writing process wasfound to be higher than before learning at a statistically significant level of .05.         3) The student’s satisfaction with learning through Brookes and Withrow’s model in English writing process was found to be overall at a high level. Keywords: Development of Grammatical Knowledge, English Writing Competence, Brookes and Withrow’s Writing Process Model